Cosmological magnetic fields from gauge-mediated supersymmetry-breaking models - Kandus, A. (2000)
We study the generation of primordial magnetic fields, coherent over cosmologically interesting scales, by gravitational creation of charged scalar particles during the reheating period. We show that magnetic fields consistent with those detected by observation may be obtained if the particle mean life τ(s) is in the range 10-14 s ≤ τ(s) ≤ 10-7 s. We apply this mechanism to minimal gauge-mediated supersymmetry-breaking models, in the case in which the lightest stau τ(l) is the next-to-lightest supersymmetric particle. We show that, for a large range of phenomenologically acceptable values of the supersymmetry-breaking scale √F, the generated primordial magnetic field can be strong enough to seed the galactic dynamo. (C) 2000 Elsevier Science B.V.